Paravalvular leak after transcatheter aortic valve replacement: Avoid it or treat it if you can!. Issue 5 (19th November 2018) - Kumar, Arnav; Block, Peter C.
Key Points: Paravalvular leaks (PVL) were more severe and frequent with medtronic core valves (MCV) when compared with Edward Sapien valves (ESV) immediately after transcatheter aortic valve replacement (TAVR). Severity and frequency of PVL improved in MCV overtime, but not in ESV. The decrease in frequency of PVL in MCV valves was earlier and more robust in the area surrounding the commissure between noncoronary cusp (NCC) to right coronary cusp (RCC) compared with other areas. Such preferential reduction of PVL was not seen in ESV.